1997
DOI: 10.1074/jbc.272.18.11736
|View full text |Cite
|
Sign up to set email alerts
|

Retroviral Gene Transfer Is Inhibited by Chondroitin Sulfate Proteoglycans/Glycosaminoglycans in Malignant Pleural Effusions

Abstract: Gene therapy may be an important adjuvant for treating cancer in the pleural space. The initial results of retroviral gene transfer to cancer cells in malignant pleural effusions revealed that transduction was markedly inhibited, and studies to characterize the inhibitory factor(s) were performed. The inhibition was contained within the soluble, rather than cellular, components of the effusions and was demonstrated with amphotropic, gibbon ape leukemia virus, and vesicular stomatitis virus-glycoprotein pseudot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
0

Year Published

1998
1998
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(33 citation statements)
references
References 40 publications
2
31
0
Order By: Relevance
“…In keeping with previous reports (1,2,14,15), soluble heparin potently inhibited the transduction of NIH 3T3 cells by MLV-A (Fig. 1).…”
Section: Resultssupporting
confidence: 77%
See 1 more Smart Citation
“…In keeping with previous reports (1,2,14,15), soluble heparin potently inhibited the transduction of NIH 3T3 cells by MLV-A (Fig. 1).…”
Section: Resultssupporting
confidence: 77%
“…The contribution of such Env-independent attachment to infectivity was not totally clear from this work, although MLV-A poorly infected certain human suspension cells which adsorbed virus particles less efficiently than adherent cell lines. Since soluble GAGs have previously been shown to inhibit transduction by MLV (1,2,14,15) and since GAGmediated interactions are involved in the initial binding of other viruses to the cell surface, we investigated whether a similar mechanism is responsible for Env-independent binding of MLV.…”
mentioning
confidence: 99%
“…Interestingly, wild-type foami viruses are resistant to complement-mediated lysis [95] and have a total insert capacity in the virion of approximately 14kb [95]. Conversely, MLV-based retroviral, lentiviral and foami viral vectors pseudotyped either with amphotropic retroviral envelopes or VSV G glycoprotein are susceptible to complement-mediated lysis [135][136][137][138] and their total insert capacity in the virion is in the range of 10kb [5]. It has been demonstrated that packaging cell lines expressing galactosyl(alpha1-3)galactosyl (alphaGal) sugars generate enveloped viruses that are more susceptible to complement attachment [136].…”
Section: Vector Systems Based On Retroviruses Lentiviruses and Foamimentioning
confidence: 99%
“…For these experiments, the vesicular stomatitis virus (VSV) envelope glycoprotein (G) was expressed from a plasmid previously constructed by us for generation of VSV-G pseudotyped MuLV vectors. 22,23 Production and testing of EIAV vectors EIAV vectors were produced by CaPO 4 -mediated transient transfection of human 293 cells, as described previously. 23 The three-plasmid cotransfection included the pEV53 gag-pol expression plasmid, the pCI-VSV-G expression plasmid and either a puro or lacZ expression vector plasmid (Figure 2).…”
Section: Viral Envelope Gene Expression Vectormentioning
confidence: 99%